INFO INFO YANG MENDEBARKAN: Punden Berundak, Toba Purba, Banjir Besar, Wawasan Nusantara, Gunung Padang - Primadi Tabrani (Jurnal Budaya Nusantara, 2014)
This article is not yet a real research; it is more as a deep reflection. But those deep reflections are worth to be researched thoroughly by experts from many fields of study integratingly. Thinking of people in land-continent with many countries as Europe is different then thinking of people in one country as Indonesia, a maritime-continent. In land-continents thinking, sea is to separte, in maritime-continent Indonesia with its islands, sea is to unite, wawasan Nusantara as old as prehistory. Each countryin a land-continent are eager to differentiate and defend to other countries by ethnic, language, religion, ideology, while in Indonsia as a maritime-continent, we is one country, several parts are slightly different but we are “one”: “Bhinneka Tunggal Ika”. In land-continent countries, a city with walls fortification, a country with great walls fortification are usual. While it is not so in Maritime-continent Indonesia, as is Trowulan the capital of the great empire Majapahit. Our school books says that the population of Indonesia comes from Asia, 5000 BC and 2000BC, while it is known that the migration of homosapiens has reach West Nusantara about 60 – 80.000 BC, and experienced the ancient Toba Mountain great explosion and the three great floods.The west theory said that Indonesia is a country between two continents and two aceans, where culture, etnic, nation, religion, etc, criss cross ofer it. So Indonesia ’has nothing’. No local genius. Nusantara people cruises the Pacific and Indian ocean before Christ, the Atlantic in the first century. What about ”Atlantis” and ”Eden in the East” situated in Sundaland, that alter the world culture, history & development? Has all this a connection with the mistery of Gunung Padang? Keywords: Land-continent thinking, Maritime-continent thinking, Wawasan Nusantara, BhinnekaTunggal Ika, Gunung Padang.